LEGASI HARUN NASUTION TENTANG PEMBAHARUAN PENDIDIKAN ISLAM DAN IMPLIKASINYA DI ERA MODERN - Hendi Sugianto; M. Yunus Abu Bakar; Ah. Zakki Fuad (UNZAH Genggong, 2023)
Harun Nasution is an Indonesian Muslim intellectual who fights for modern Islamic education and is open to science and technology. For him, renewal is a necessity for Islamic education, because Islamic education must have relevance to the dynamics of social life. This study aims to reveal the concept of renewal of Islamic education carried out by Harun Nasution. The method used in this research is descriptive qualitative with the type of library research, where the data used includes bibliographical data, articles, books, and other documents. The results of this study indicate that the legacy of Harun Nasution's thoughts in Islamic education is educational reform including; first, the goal of integrated Islamic education; second, educational curriculum; third, Islamic education methods; and fourth, Islamic education teachers. The implication of the above thoughts is the formation of individuals who have the ability to think critically, understand and fight for humanitarian principles, and can contribute positively to society.Keywords: Harun Nasution, Legacy, Education, Modern